Design of nature-inspired patterns on knitted fabrics for directional transportation of sweat and study of their performances - Liu, Li-Yan; Liu, Guo-Hua; Shou, Bing-Bing; Li, Ting-Ting; Ren, Hai-Tao; Lin, Jia-Horng; Lou, Ching-Wen; Xu, Yu-Man (Textile research journal, 2025)
The human body in a hot environment or during intense training will sweat a lot. Traditional cotton fabrics are soft and breathable, but they tend to absorb moisture easily and evaporate it slowly, which makes people feel cold and wet. Sweat staying on fabrics for a long time could also cause bacteria to grow. Thus, it is necessary to transport the excessive sweat from the gathering section to the collection points along the surface paths in time to minimize such problems. The mechanism of directional water transport of desert beetles, cacti, nepenthes, and river meanders was referenced in this paper. The paths in dot, tree, V-shape, and river meander patterns were designed and manufactured from the inspiration of these natural architectures. The paths were coated on the surfaces of selected knitted fabrics with different structures through a one-step coating process. The optimal recipe of hydrophobic solution was determined when 0.1 g hydroxyethyl-cellulose (HEC) was added into MS-S002 solution. The results showed that sweat movement is mainly influenced by FL, FWD, FG, and knitted structure. The continuous and enclosed paths such as tree and river contribute to a better sweat moving track than those of dot and V-shape ones. Terry structure is more suitable for surface sweat transport than plain and pique. The highest movement speed of the terry structure with a tree pattern reaches 0.43 cm/s, followed by that of the terry structure with river pattern 0.35 cm/s. The coated fabrics also have ideal moisture and air permeability for wearing.